Phenotypic characterization of Hanwoo (native Korean cattle) cloned from somatic cells of a single adult - Yang, B.C., National Institute of Animal Science, RDA, Suwon, Republic of Korea; Lee, S.H., National Institute of Animal Science, RDA, Suwon, Republic of Korea; Hwang, S.S., National Institute of Animal Science, RDA, Suwon, Republic of Korea; Lee, H.C., National Institute of Animal Science, RDA, Suwon, Republic of Korea; Im, G.S., National Institute of Animal Science, RDA, Suwon, Republic of Korea; Kim, D.H., National Institute of Animal Science, RDA, Suwon, Republic of Korea; Lee, D.K., National Institute of Animal Science, RDA, Suwon, Republic of Korea; Lee, K.T., National Institute of Animal Science, RDA, Suwon, Republic of Korea; Jeon, I.S., National Institute of Animal Science, RDA, Suwon, Republic of Korea; Oh, S.J., National Institute of Animal Science, RDA, Suwon, Republic of Korea; Park, S.B., National Institute of Animal Science, RDA, Suwon, Republic of Korea (BMB reports, 2012)
We investigated phenotypic differences in Hanwoo cattle cloned from somatic cells of a single adult. Ten genetically identical Hanwoo were generated by somatic cell nuclear transfer from a single adult. Weights at birth, growing pattern, horn and noseprint patterns were characterized to investigate phenotypic differences. The weights of clones at 6 and 12 months were slightly heavier than that of the donor. A horn pattern analysis revealed that seven clones had exactly the same horn pattern as the donor cow, whereas three were different. Although similarities such as general appearance can often be used to identify individual cloned animals, no study has characterized noseprint patterns for this end. A noseprint pattern analysis of all surviving clones showed that all eight animals had distinct noseprints. Four were similar to the donor, and the remaining four had more secondary-like characteristics.